2019
DOI: 10.1093/icvts/ivz129
|View full text |Cite
|
Sign up to set email alerts
|

Open radial artery harvesting better preserves endothelial function compared to the endoscopic approach

Abstract: OBJECTIVES Both the open and endovascular techniques are commonly used for harvesting the radial artery (ORAH and ERAH, respectively), and yet, very little is known about the effects of these 2 techniques on endothelial integrity and function of the radial artery (RA). The aim of this study was to assess the endothelial integrity and function of RA harvested using the 2 approaches. METHODS Two independent surgical teams worki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 29 publications
(35 reference statements)
1
8
0
2
Order By: Relevance
“…In current study we also reported less neurological complications in the endoscopic harvest technique. These findings were also similar to a prospective study in which they reported that the neurological complication reduces from 10 to 0% [19,20]. In our study we We also lack the long term follow up of patients regarding graft patency for each group.…”
Section: Resultssupporting
confidence: 91%
“…In current study we also reported less neurological complications in the endoscopic harvest technique. These findings were also similar to a prospective study in which they reported that the neurological complication reduces from 10 to 0% [19,20]. In our study we We also lack the long term follow up of patients regarding graft patency for each group.…”
Section: Resultssupporting
confidence: 91%
“…The endoscopic procedure of EAH takes place in a very narrow space, raising the concern of potential mechanical injuries to the conduits, especially on the endothelium. A pathologic examination also showed that RA from OAH had a significantly higher vasodilation response to medications [ 54 ]. However, our statistical analysis suggested that there was no difference in the patency rate between OAH and EAH (RR = 0.91, 95% CI = 0.79 to 1.06, p = 0.23).…”
Section: Discussionmentioning
confidence: 99%
“… 17 , 18 Conversely others have found superior endothelial integrity with ORAH, 18 , 19 and better preservation of endothelial-dependant vasodilatation. 20 ORAH and ERAH are both applicable and after 25 years of evolution both techniques provide similar patency (approximately 90% at 6-10 years) and clinical outcomes. 4 , 16 , 21 ERAH results in better cosmesis and fewer infections.…”
Section: Anatomymentioning
confidence: 93%